(untitled) (Chemical Engineering Research Bulletin, 2016)
A regression model for simulating residence time distribution (RTD) of turbulent flows in helical static mixers is proposed and developed to predict the residence time distribution in static mixers. An efficient method is required to estimate the RTD and the sole means of achieving this is through detailed regression model. The RTD was calculated numerically by regression model. The results of the regression model, i.e. predicted RTD is presented in terms of different volumetric flow rate to illustrate the complicated flow patterns that drive the mixing process in helical static mixers. The regression model is found to fit the experimental RTD with a high degree of correlation. Chemical Engineering Research Bulletin 18(2015) 23-29